Efforts of Discovery and Development of Pancoair Sport as A Recreational Sport in Order to Increase The Attraction of Water Tourism in Indonesia and Foreign Countries - Syahri Alhusin; Shodiq Hutomono (Journal Of Social Research, 2021)
In order to increase innovative and creative work as a lecturer, I try to create a real work that is hoped to be able to give positive benefits in the development. As a lecturer of entrepreneurship subject for the students of Health and Education of Teacher Training and Education Faculty of UTP, so I try to engineer a kind of new sport that I name “Panco Air”. Inspiration of “Panco Air” came from smashing game that I had done since I was in grade 5 (an elementary school) together with my friends in my age. The play site was on a pathway bridge over a river 5 meters wide and 1.2 meters deep located in Srikaton village, Tugumulyo subdistrict, Musi Rawas Regency, South Sumatra Paancoair socialization has been carried out with various activities. In order to researching and developing and mass-producing the Pancoair Sport Pedestal, a Research and Development team will be formed from researchers from various fields of science (multidisciplinary) and in collaboration with entrepreneurs.